A meta-analysis to observe silage microbiome differentiated by the use of inoculant and type of raw material - Ridwan, Roni; Abdelbagi, Mohammed; Sofyan, Ahmad; Fidriyanto, Rusli; Astuti, Wulansih D.; Fitri, Ainissya; Sholikin, Mohammad M.; Rohmatussolihat,; Sarwono, Ki A.; Jayanegara, Anuraga; Widyastuti, Yantyati (Frontiers in Microbiology, 2023)
Silage fermentation is naturally carried out by lactic acid bacteria (LAB) to mainly produce lactic acid (LA) and other organic acids as preservatives. Along with fermentation time, the growth of LAB will replace and suppress undesirable microorganisms. This meta-analysis study aimed to explore silage microbiome differentiated by LAB inoculants and type of raw materials. A total of 37 articles with 185 studies and 475 datasets were used for building up the meta-database. Data were subjected to the mixed model methodology. The parameters observed were silage quality and silage microbiome post-ensiling process. Results revealed that four bacterial genera along with Weissella dominated the post-ensiling process. The addition of lactic acid inoculants in the silage has increased the abundance of Lactobacillus spp. and decreased the Shannon index significantly. Moreover, the abundance of both L. plantarum and L. buchneri increased, and subsequently, Weissella, Pseudomonas, Proteobacteria, pH value, ammoniacal nitrogen (NH3-N), coliforms, and the yeasts were decreased significantly due to the addition of LAB inoculants in silage (p < 0.05). Environmental factors such as temperature affected the existence of Pseudomonas, Exiguobacterium, and Acinetobacter. However, the dry matter, LA, acetic acid (AA), the ratio of LA to AA, and the LAB population were enhanced significantly (p < 0.05). Among the LAB types, the lowest abundance of Pseudomonas was due to the LAB group, while the lowest abundance of Weissella and Proteobacteria was due to the addition of the combined LAB group. In conclusion, the addition of LAB is effectively enhancing the silage microbiome and silage quality by altering bacterial diversity and the metabolic products of the silage materials for safe preservation.